An Economic Evaluation of the Impact of Using Rapport-Based Interviewing Approaches With Child Sexual Abuse Suspects - Giles, Susan; Alison, Laurence; Christiansen, Paul; Humann, Michael; Alison, Emily; Tejeiro, Ricardo (Frontiers in Psychology, 2021)
Two studies examined whether rapport-based interviewing with CSA suspects provides greater interview yield that could result in overall cost-savings to the investigation. First, multi-level modelling was applied to 35 naturalistic CSA suspect interviews to establish whether rapport-based interviewing techniques increase ‘yield’- defined as information of investigative value. The ORBIT coding manual was used to code interviews; it includes an assessment of both interpersonal adaptive and maladaptive rapport-based interviewer engagement as well as motivational interviewing (MI) strategies. The impact of these two strands (interpersonal and MI) on extracting information of investigative value (including strengthening a case for court and safeguarding) were examined. Adaptive interpersonal strategies increased case strengthening and safeguarding yield, with motivational interviewing having the largest impact on safeguarding yield. Both strategies increase the likelihood of gaining additional types of economic yield. Maladaptive interviewer strategies reduced case strengthening and different types of economic yield. In study two, literature-based economic estimates were applied to establish the potential cost benefits from following national ORBIT rapport training. Further training in adaptive and motivational interviewing could contribute cost savings between £19-£78 million (annual unit costs) increasing to £238-£972 million (lifetime costs) for online CSA across England and Wales; and £157-£639 million (annual unit costs) increasing to £2-£8 billion (lifetime costs) for all CSA. Failure to commit training resource to this, or an alternative strategy, could mean the cost burden attributable to maladaptive interviewing (between £1-£6 million for online CSA and £12-£48 million for all CSA) is not successfully averted.